Digital Marketing Communication Strategy in Facing Umrah Travel Business Competition in Makassar City: JEL Classification: M31, L83, Z32, D83, L86, M37 - Pusvitasari, Dwi; Sukmarini, Andi Vita; Samad, Abdul (Newinera Publisher, 2025)
This study discusses the digital marketing communication strategy implemented by PT. Wisata Iman in facing the competition of Umrah travel business in Makassar City. Amid the increasing use of social media and changes in the behavior of prospective Umrah pilgrims, the company utilizes digital platforms—especially Instagram—to expand the reach of promotions, build trust, and increase interaction with prospective customers. Through a descriptive qualitative approach, data was obtained from in-depth interviews with internal parties and customers of PT. Wisata Iman. The results of the study indicate that a communication strategy based on educational, inspirational, and testimonial content through Instagram can increase the trust and interest of prospective pilgrims. However, the company also faces challenges such as limited advertising budget, tight competition, and limited resources in digital content management. Therefore, an integrated strategy with the use of SEO, email marketing, and collaboration with influencers is the key to increasing the effectiveness of digital promotions and expanding the market. This study contributes to understanding the strategic role of digital marketing communication in the religious travel industry.